WHAT WILL THE FUTURE SOCIETY BE LIKE? - O. V. Gutorovich (Дискурс, 2019)
The article focuses on the challenges of rapid progress in science and technology in the 21st century. The author aims to show the extensive changes in this area, which is demonstrated by convergent technologies development, and to focus on the consequences that individuals and society will face in the future. The article characterizes the forming network society defined by computer networks. Its essence and structural principles are specified, and the features of network culture are studied. The author also focuses on the fact that the consequences of scientific and technological progress are associated with different risks, and both positive and negative effects are possible. Yet an individual is still to accept and master the paradigms and principles the future society will be formed on.